2012
DOI: 10.1007/s00262-012-1311-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor effects of DC-activated CIKs to chemotherapy treatment in a single cohort of advanced non-small-cell lung cancer patients

Abstract: Cytokine-induced killer (CIK) cells show cytolytic activity against tumor. The purpose of this study was to evaluate the antitumor effect of dendritic cell (DC)-activated CIK cells in vitro and their clinical efficacy of DC-activated CIK cells in combination with chemotherapy (abbreviated below as chemotherapy plus DC + CIK) in patients with advanced non-small-cell lung cancer (NSCLC). A paired study was performed between 61 patients treated with chemotherapy alone (group 1) and 61 patients treated with chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 23 publications
2
73
0
Order By: Relevance
“…1 Approximately 80% to 85% of lung malignancies are NSCLC, with a 5-y survival rate of only 15%. 2,3 Surgery is the most effective treatment for NSCLC. However, 60% to 70% of patients with NSCLC experience postoperative recurrence and metastasis, resulting in a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Approximately 80% to 85% of lung malignancies are NSCLC, with a 5-y survival rate of only 15%. 2,3 Surgery is the most effective treatment for NSCLC. However, 60% to 70% of patients with NSCLC experience postoperative recurrence and metastasis, resulting in a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…A series of clinical studies have shown that adjuvant CIT, such as CIK cells and NK cells, can lead to promising antitumor effects on various cancers, [17][18][19][20][21] including lung cancer. 3,[22][23][24][25][26] Several reviews and meta-analysis reports have also demonstrated the safety and effectiveness of adjuvant CIT in clinics. [27][28][29][30] However, the patterns of CIT require thorough investigation in order to achieve optimal outcome and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of immune cells, such as lymphokine-activated killer cells (9), tumor-infiltrating lymphocytes (10) and anti-CD3 monoclonal antibody-induced killer cells (11) have shown efficacy in advanced cancers. Among these cells, cytokine-induced killer (CIK) cells have several advantages compared with traditional immune cells, such as proliferating rapidly in vitro, exhibiting intensified antitumor activity and a broader spectrum of targeted tumors, and being associated with less severe side effects, which qualifies them as one of the most promising treatments, particularly for patients with advanced cancer (6,(12)(13)(14)(15)(16)(17). It is noteworthy that the antitumor activity of CIK cells may be activated…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary approaches are required to develop novel treatments for advanced NSCLC (7). One of these multidisciplinary approaches is immunotherapy (7,8), an important and effective method in cancer treatment, particularly for advanced-stage disease (9).…”
Section: Introductionmentioning
confidence: 99%